The effect of social information from live demonstrators compared to video playback on blue tit foraging decisions - Hämäläinen, Liisa (PeerJ, 2019)
Video playback provides a promising method to study social interactions, and the number of video playback experiments has been growing in recent years. Using videos has advantages over live individuals as it increases the repeatability of demonstrations, and enables researchers to manipulate the features of the presented stimulus. How observers respond to video playback might, however, differ among species, and the efficacy of video playback should be validated by investigating if individuals’ responses to videos are comparable to their responses to live demonstrators. Here, we use a novel foraging task to compare blue tits’ (Cyanistes caeruleus) responses to social information from a live conspecific vs video playback. Birds first received social information about the location of food, and were then presented with a three-choice foraging task where they could search for food from locations marked with different symbols (cross, square, plain white). Two control groups saw only a foraging tray with similar symbols but no information about the location of food. We predicted that socially educated birds would prefer the same location where a demonstrator had foraged, but we found no evidence that birds copied a demonstrator’s choice, regardless of how social information was presented. Social information, however, had an influence on blue tits’ foraging choices, as socially educated birds seemed to form a stronger preference for a square symbol (against two other options, cross and plain white) than the control birds. Our results suggest that blue tits respond to video playback of a conspecific similarly as to a live bird, but how they use this social information in their foraging decisions, remains unclear.